Cancer Classification Using Gaussian Naive Bayes Algorithm - Kamel, Hajer; Abdulah, Dhahir; Al-Tuwaijari, Jamal M. (2019 International Engineering Conference (IEC), 2019)
Cancer is one of the most deadly diseases in the world and it is a subject of concern because until till date they cannot found the real treatment for this disease. If and only if this disease is detected in early stage, patients having this disease can be saved. If it is detected in latter stage then chance of survival will be very less. Because of this, early and true diagnosis is an important issue and plays a key role to cure this disease. In the work, Gaussian Naive Bayes algorithm is used for classification cancer. The algorithm is tested by applying it on two datasets in which the first is Wisconsin Breast Cancer dataset (WBCD) and the second is lung cancer dataset. The evaluation results of the proposed algorithm have achieved 98% accuracy of predicting breast cancer and 90% of predicting lung cancer.